The Continuity Of Religious Moderation: A Comparative Study Of Religious Tolerance From The Mughal Dynasty To Contemporary Indonesia - Putri, Mufatihatuttaubah Rorom Ika (Moderatio: Jurnal Moderasi Beragama, 2025)
The concept of religious tolerance is not new. Clear evidence that religious tolerance has been implemented since ancient times can be seen in the policies implemented by the Mughal Dynasty. This research aims to explore the practice of religious tolerance from the Mughal Dynasty to Contemporary Indonesia, focusing on the continuity and changes in implementation in each period. The method used is a qualitative-comparative approach that involves analyzing historical documents and academic literature. The results of the study show that religious tolerance already existed during the Mughal Dynasty, it was marked by policies such as Sulh-i Khul and Ibadat Khana that aimed to unite various religions. In addition, the concept of Din-i-Ilahi introduced by Akbar tried to integrate the values of various religious traditions. In Indonesia, similar efforts are made through religious institutions and religious moderation education to maintain interfaith harmony. Both contexts show that tolerance can flourish through inclusive policies and constructive dialogue, although the challenges are different. Commitment to building a harmonious and respectful society remains key in dealing with diversity.